Comparative Analysis of Rhizosphere Microbiomes of Southern Highbush Blueberry (Vaccinium corymbosum L.), Darrow’s Blueberry (V. darrowii Camp), and Rabbiteye Blueberry (V. virgatum Aiton) - Li, Jiangang; Mavrodi, Olga V.; Hou, Jinfeng; Blackmon, Chazden; Babiker, Ebrahiem M.; Mavrodi, Dmitri V. (Frontiers in Microbiology, 2020)
Plants are inhabited by millions of parasitic, commensal, and mutualistic microorganisms that coexist in complex ecological communities, and profoundly affects the plant’s productivity, health, and capacity to cope with environmental stress. Therefore, a better understanding of the rhizosphere microbiome may open a yet untapped avenue for the rational exploitation of beneficial plant-microbe interactions in modern agriculture. Blueberries encompass several wild and cultivated species of shrubs of the genus Vaccinium that are native to North America. They are grown commercially for the production of fruits, which are considered a health food due to the rich content of minerals, trace elements, and phenolic compounds with antioxidant, antitumor, and anti-inﬂammatory properties. Despite a long history of breeding and extensive commercial use, remarkably little is known about the composition and function of the blueberry root microbiome. To address this gap, we employed molecular approaches to characterize and compare microbial communities inhabiting the roots of rabbiteye blueberry (Vaccinium virgatum), Darrow’s blueberry (V. darrowii), and southern highbush blueberry (an interspecific hybrid of V. corymbosum and V. darrowii). Our results revealed that these plant species share a common core rhizobiome, but at the same time differ significantly in the diversity, relative abundance, richness, and evenness of multiple groups of prokaryotic and eukaryotic microorganisms. Although the host signature effects were especially pronounced at the plant species level, we also observed genotype-level variations in the distribution of specific microbial taxa, which suggests that the assembly of the blueberry microbiome is shaped by the plant genotype and modifications associated with the domestication and breeding of members of the Vaccinium genus. We also demonstrated that the studied Vaccinium species differ in the abundance of beneficial rhizobacteria and ericoid mycorrhizal fungi, which play a vital role in their adaptation to soils with low pH and slow turnover of organic matter.